Aspergillus Pseudoaneurysm Post Aortic Valve Replacement - Perdomo, Joel (Aorta (Stamford), 2014)
Thoracic aortic mycotic aneurysms caused by Aspergillus fumigatus postoperatively are rare and devastating complications. These cases are usually attributed to intraoperative contamination of surgical equipment. We present a patient who had an ascending aortic mycotic aneurysm 20 weeks post aortic valve replacement. A high index of suspicion allowed for diagnosis and prompt treatment, although the patient presented in an unusual manner. Treatment included both medical and surgical therapy to minimize morbidity and mortality. Despite treatment our patient suffered long-lasting consequences due to the aggressive nature of the disease. Cases presented in the literature and this experience show that a high index of suspicion must be maintained in such patients regardless of immune status and postoperative interval, in order to avoid long-lasting sequelae.